(untitled) (Res Medica, 2014)
Background: Allergic bronchopulmonary aspergillosis (ABPA) is a persistent problem for many cystic fibrosis (CF) patients. It is a challenging condition to diagnose and manage. Aim: The CF team at Alder Hey Children’s Hospital aimed to assess how consistently and effectively they were managing the condition. A diagnosis and management monitoring tool was used to systematically draw data for auditing. Methods: Out of 87 patients under the care of the CF team, 20 had previously been diagnosed with ABPA. 60% had 4 out of the 4 minimal diagnostic criteria. 75% grew cultures positive for A. fumigatus at some point since their diagnosis of ABPA. All patients had received prednisolone therapy at some point since diagnosis, with 7 patients receiving the maximum starting dose of 40 mg and 1.29 mg/kg for those below maximum dose. 14 patients were prescribed antifungal therapy. 5 patients had levels ordered when they started the therapy, 5 had levels ordered between 45 and 1149 days after prescription, and 3 have had no levels ordered to date. A second audit was performed one year later to complete the audit cycle. Results: This cohort of patients had a much higher prevalence of ABPA than the general CF population. Discussion: Research into the relationship between ABPA exacerbation and concurrent infections or antibiotic therapy could help identify risk factors for developing an exacerbation. There should be discussions about how to improve the consistency in initial dosing of prednisolone, considering guidelines. Conclusion: There should be more itraconazole levels taken to ensure safety and effectiveness of antifungal therapy.